2018
DOI: 10.1063/1.5010431
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of temporally and spatially periodic modulated wave trains

Abstract: A number of studies on steep nonlinear waves were conducted experimentally with the temporally periodic and spatially evolving (TPSE) wave trains and numerically with the spatially periodic and temporally evolving (SPTE) ones. The present study revealed that, in the vicinity of their maximum crest height, the wave profiles of TPSE and SPTE modulated wave trains resemble each other. From the investigation of the Akhmediev-breather solution of the nonlinear Schrödinger equation (NLSE), it is revealed that the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The estimated error in the crest height of regular waves with a wavelength of 3 m and wave height between 10 and 20 cm is less than 4% in this stereo-imaging scheme [36]. Note that the standard deviation of the wave-maker motion was found to be 1.065 times larger than the given signal owing to a problem with controlling the mechanical wave maker [31]. Therefore, the experimental results presented in Section 3 are corrected by a factor of 1.065 for comparison with the HOSM simulation.…”
Section: Tank Experimentsmentioning
confidence: 74%
See 1 more Smart Citation
“…The estimated error in the crest height of regular waves with a wavelength of 3 m and wave height between 10 and 20 cm is less than 4% in this stereo-imaging scheme [36]. Note that the standard deviation of the wave-maker motion was found to be 1.065 times larger than the given signal owing to a problem with controlling the mechanical wave maker [31]. Therefore, the experimental results presented in Section 3 are corrected by a factor of 1.065 for comparison with the HOSM simulation.…”
Section: Tank Experimentsmentioning
confidence: 74%
“…We numerically simulated the temporal evolution of spatially periodic deep-water modulated wave trains using the HOSM [28,29] in the same manner as in our preceding studies [31,32]. The HOSM numerically solves Laplace's equation (∇ 𝜙 = 0) subject to nonlinear kinematic and dynamic free-surface boundary conditions with respect to the surface elevation 𝜁 and velocity potential on the free surface, 𝛷 = 𝜙| [22]:…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In the cases of marginal drift speed, the wave packets remain indeed symmetric at all stages of evolution. Moreover, the shape of the unstable envelopes in the latter cases resembles the propagation of the ABs within the framework of the space-NLS (the framework evolving the wave packets along the temporal co-ordinate t) [35,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that in some cases it is inappropriate to use the linear dispersion relation for the post-processing of experimental data. Houtani et al (2018a) and Houtani, Waseda & Tanizawa (2018b) have demonstrated that the dispersion characteristics of the Akhmediev breather solution to the nonlinear Schrödinger equation in deep water deviates significantly from the linear relationship (2.13). It was also shown that these findings extend beyond the applicability of nonlinear Schrödinger equation.…”
Section: Dispersion Variationmentioning
confidence: 99%